Rentabilité, risque et diversification internationale des banques à charte canadiennes - Cosset, Jean-Claude; Lampron, Laurent (L'Actualité économique)

(untitled) (HEC Montréal, 1982)
AbstractThis paper examines in the framework of the asset pricing theory how the internationalization of banking operations has influenced the returns and the risk of Canadian chartered banks.Banking statistics reveal that in the last decade the Canadian banks have greatly increased their foreign operations. These statistics also indicate that the development of international banking operations has been more remarkable than that of domestic banking operations. Contrary to some banks' claims, our evidence reveals that average returns on foreign operations have been inferior to those obtained on purely Canadian operations. Moreover, in conformity with the asset pricing theory we have found that the systematic risk of international operations is smaller than that of domestic operations. Our results suggest that Canadian chartered banks have reduced their overall risk in internationalizing their operations.